Corporate governance, capital market discipline and the returns on investment; Corporate Governance, Kapitalmarktdisziplinierung und die Renditen von Unternehmensinvestitionen - Klaus Gugler; Dennis C. Mueller; B. Burcin Yurtoglu (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2001)
We analyze the impact of corporate governance institutions, ownership structures and external capital market constraints on company returns on investment by using a sample of more than 19,000 companies from 61 countries across the world. We show that (1) of these three sets of institutions, the origin of a country's legal system proves to be the most important. Companies in countries with English-origin legal systems earn returns on investment that are at least as large as the cost of capital. (2) Differences in investment performance related to a country's legal system dominate differences related to ownership structure. (3) Strong external capital markets improve the investment performance of companies. – – Dieses Papier analysiert den Einfluß von Corporate Governance Institutionen, Eigentümerstrukturen und externen Kapitalmärkten auf die Renditen von Investitionen für ein Sample von mehr als 19.000 Unternehmen aus 61 Ländern weltweit. Wir zeigen, dass von diesen drei Institutionen (1) die Herkunft des Rechtssystems eines Landes der wichtigste Faktor ist. Unternehmen in Ländern mit Rechtssystemen englischer Herkunft verdienen Renditen, die die Kapitalkosten im Durchschnitt abdecken. (2) Unterschiede im Rechtssystem eines Landes dominieren Unterschiede in der Eigentümerstruktur. (3) Funktionierende externe Kapitalmärkte verbessern die Performance von Investitionen.
Keywords: G32; G34; L21; 330; Return on Investment; Ownership Structure; Corporate Governance; Capital Market